Circulating insulin‐like growth factor‐I, total and free testosterone concentrations and prostate cancer risk in 200 000 men in UK Biobank - Watts, EL; Fensom, GK; Smith Byrne, K; Perez-Cornago, A; Allen, NE; Knuppel, A; Gunter, MJ; Holmes, MV; Martin, RM; Murphy, N; Tsilidis, KK; Yeap, BB; et al. (Wiley, 2020)
Insulin‐like growth factor‐I (IGF‐I) and testosterone have been implicated in prostate cancer aetiology. Using data from a large prospective full‐cohort with standardised assays and repeat blood measurements, and genetic data from an international consortium, we investigated the associations of circulating IGF‐I, sex hormone‐binding globulin (SHBG), and total and calculated free testosterone concentrations with prostate cancer incidence and mortality. For prospective analyses, risk was estimated using multivariable‐adjusted Cox regression in 199 698 male UK Biobank participants. Hazard ratios (HRs) were corrected for regression dilution bias using repeat hormone measurements from a subsample. Two‐sample Mendelian randomisation (MR) analysis of IGF‐I and risk used genetic instruments identified from UK Biobank men and genetic outcome data from the PRACTICAL consortium (79 148 cases and 61 106 controls). We used cis‐ and all (cis and trans) SNP MR approaches. A total of 5402 men were diagnosed with and 295 died from prostate cancer (mean follow‐up 6.9 years). Higher circulating IGF‐I was associated with elevated prostate cancer diagnosis (HR per 5 nmol/L increment = 1.09, 95% CI 1.05‐1.12) and mortality (HR per 5 nmol/L increment = 1.15, 1.02‐1.29). MR analyses also supported the role of IGF‐I in prostate cancer diagnosis (cis‐MR odds ratio per 5 nmol/L increment = 1.34, 1.07‐1.68). In observational analyses, higher free testosterone was associated with a higher risk of prostate cancer (HR per 50 pmol/L increment = 1.10, 1.05‐1.15). Higher SHBG was associated with a lower risk (HR per 10 nmol/L increment = 0.95, 0.94‐0.97), neither was associated with prostate cancer mortality. Total testosterone was not associated with prostate cancer. These findings implicate IGF‐I and free testosterone in prostate cancer development and/or progression.